2011
DOI: 10.1094/mpmi-09-10-0196
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Xanthomonas campestris pv. vesicatoria Type III Effectors in Yeast Affects Cell Growth and Viability

Abstract: The gram-negative bacterium Xanthomonas campestris pv. vesicatoria is the causal agent of spot disease in tomato and pepper. X. campestris pv. vesicatoria pathogenicity depends on a type III secretion system delivering effector proteins into the host cells. We hypothesized that some X. campestris pv. vesicatoria effectors target conserved eukaryotic cellular processes and examined phenotypes induced by their expression in yeast. Out of 21 effectors tested, 14 inhibited yeast growth in normal or stress conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 54 publications
4
52
0
Order By: Relevance
“…6B). Similar to our results, it was shown previously that the Xanthomonas campestris effector XopC does not inhibit yeast growth, but when it was examined in the presence of caffeine, it caused a strong growth inhibition (84). Notably, this effector was found to contain a HAD domain (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6B). Similar to our results, it was shown previously that the Xanthomonas campestris effector XopC does not inhibit yeast growth, but when it was examined in the presence of caffeine, it caused a strong growth inhibition (84). Notably, this effector was found to contain a HAD domain (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, this effector was found to contain a HAD domain (Fig. 6A), and mutagenesis of conserved amino acids of this domain abolished the growth inhibition by XopC on yeast growth (84). The results showing the importance of the HAD domain for the activity of the C. burnetii CBU1676 and CBU0885 effectors and the analysis in yeast which indicates that these two effectors modulate a MAP kinase pathway suggest that these two effectors modulate the phosphorylation state of one or more components in the MAP kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, our computational search of available OsSWEET14 promoter sequences raises the possibility that this potent virulence factor might favour colonization of Xoo on the different rice species O. sativa and O. brachyantha. So far, the possibility that TALEs of one bacterial strain support virulence in different host species has not been explored, but it is typical for type III effectors that they function in different plants and even non-plants 51,52 . Further analysis of natural TALEs with aberrant repeats and their target promoters will clarify the role of these unique virulence factors for the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous findings showing that expression of AvrBs1 in yeast causes sensitivity to NaCl and sorbitol that are known inducers of the HOG pathway. 28 In conclusion, our screen identified five Xanthomonas effectors that suppressed cell death induced by components of immunity-associated MAP kinase cascades. Furthermore we found that AvrBs1 suppresses activation of the HOG MAPK pathway in yeast, suggesting that this effector targets a signaling component that is conserved in eukaryotic organisms.…”
mentioning
confidence: 84%